Hidden Injustice and Anti-Science - Laurel Smith-Doerr (Engaging Science, Technology, and Society, 2020)
This essay responds to the five articles on Anti-Science in this journal issue by discussing a significant theme identified across all of them: hidden injustice. Some of the ways that injustice is hidden by organizational forces related to anti-science are identified. In response, the essay points to the need for empirical data on anti-science policies, a symmetric approach to anti-science contexts, and institutional analysis of anti-science power imbalances. Additionally, a reflexive question about whether anti-science analysis in STS leads the field toward racial justice is raised. The essay calls for further organizational level research with a critical STS lens to uncover hidden injustice.